2006
DOI: 10.1021/cm060997q
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Luminescence from Single-Crystalline C60·1m-xylene Nanorods

Abstract: Single-crystalline C 60 ‚1m-xylene nanorods with a hexagonal structure were successfully synthesized by evaporating a C 60 solution in m-xylene at room temperature. The ratio of the length to the diameter of the nanorods can be controlled in the range of ≈10 to over 1000 for different applications. The photoluminescence (PL) intensity of the nanorods is about 2 orders of magnitude higher than that for pristine C 60 crystals in air. Both UV and Raman results indicate that there is no charge transfer between C 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
136
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 37 publications
16
136
1
Order By: Relevance
“…1. The XRD pattern at ambient pressure is well indexed as individual C 60 molecules occupying the lattice points of a hexagonal close-packed (hcp) structure (space group P6 3 ) with lattice constants a = 2.3761 nm and c = 1.0120 nm, in good agreement with literature values (18,22,23). During compression up to 60.1 GPa, the diffraction peaks gradually broaden, weaken, and shift to higher Q (reciprocal lattice vector).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…1. The XRD pattern at ambient pressure is well indexed as individual C 60 molecules occupying the lattice points of a hexagonal close-packed (hcp) structure (space group P6 3 ) with lattice constants a = 2.3761 nm and c = 1.0120 nm, in good agreement with literature values (18,22,23). During compression up to 60.1 GPa, the diffraction peaks gradually broaden, weaken, and shift to higher Q (reciprocal lattice vector).…”
supporting
confidence: 88%
“…For example, most birds, many arthropods, and some fish have UV vision (22), and many snakes, such as pit vipers, can sense IR light using specialized organs (23). Semiconductor technology has expanded our ability to see into the IR (24), and we explored techniques for camouflage or display in the IR.…”
Section: Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] In particular, a great expectation was placed on the biological and biomedical applications of tubular nanomaterials. [7][8][9] As one of the most important materials of the carbon family, C 60 has many unique properties, such as, fluorescence and biological activities, [10][11][12] which makes it a potential functional material. Recent research focuses on exploring practical applications from nanocrystals with C 60 molecules as building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[12,17] In C 60 bulk crystals, the high pressure and high temperature (HPHT) method has proved to be an efficient tool to obtain various polymeric phases without introducing other components. [16][17][18] Our previous work on the polymerization of C 60 nanorods and nanosheets suggested that C 60 nanocrystals could also be polymerized after such treatments, and the morphology and crystal size greatly influenced the polymerization process of C 60 .…”
Section: Introductionmentioning
confidence: 99%